2015
DOI: 10.2903/j.efsa.2015.4164
|View full text |Cite
|
Sign up to set email alerts
|

Update on oral vaccination of foxes and raccoon dogs against rabies

Abstract: An assessment of a report issued by the European Commission in 2002 is presented about the oral vaccination of foxes against rabies, as well as additional topics such as the rabies aetiology and its occurrence in Europe, the target species for oral vaccination, i.e. foxes and raccoon dogs, the oral vaccines available and their thermostability, rabies surveillance and monitoring, and the recent international guidelines for rabies surveillance are discussed. Foxes are the only known reservoir for rabies in Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 91 publications
(191 reference statements)
1
9
0
Order By: Relevance
“…We found that consecutive and coordinated vaccination across geographical regions is required to rapidly control and eliminate rabies. This confirms previous findings [8] and is in accordance with EU recommendations [18], appearing to result from the need to maintain sufficient herd immunity in the face of seasonal birth pulses. Autumn vaccination campaigns had a greater impact on increasing the probability of elimination and reducing time to elimination across a range of epidemiological scenarios.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that consecutive and coordinated vaccination across geographical regions is required to rapidly control and eliminate rabies. This confirms previous findings [8] and is in accordance with EU recommendations [18], appearing to result from the need to maintain sufficient herd immunity in the face of seasonal birth pulses. Autumn vaccination campaigns had a greater impact on increasing the probability of elimination and reducing time to elimination across a range of epidemiological scenarios.…”
Section: Discussionsupporting
confidence: 92%
“…relation to demographic processes should be explored, taking into account appropriate practical considerations. For fox rabies, timing of ORV campaigns was determined based on factors including immune competence [21,22], vaccine sensitivity to high temperatures [23], levels of herd immunity and deployment costs [18]. Connectivity generally plays a key role in disease persistence [24,25] and the size of host populations influences time to control [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a key reference is the scientific report on the oral vaccination of foxes against rabies [34], covering the practical and organizational aspects to consider. The European Food Safety Authority (EFSA) updated this report with scientific panels in 2010 [35] and 2015 [36]. Such guidelines were drafted in line with WHO and OIE rabies recommendations [7,[37][38][39][40][41].…”
Section: Technical Supportmentioning
confidence: 99%
“…As the golden jackal (Canis aureus) could be a potential host [43], and following its recent geographical expansion [44], this species has been included since a few years of the monitoring of vaccination effectiveness. ORV campaigns are classically undertaken by aerial distribution of the vaccine baits twice a year, at a density around 20-25 baits/km 2 [34][35][36]. Campaigns are organized in spring and autumn to match with the red fox biology [45] and optimal temperature conditions.…”
Section: Key Control Parameters Of Vaccines and Vaccinationmentioning
confidence: 99%